Modeling dynamic anisotropic behaviour and spall failure in commercial aluminium alloys AA7010 - Mohd Nor, M. K.; Ma’at, N.; Ho, C. S. (Springer Nature, 2018)
This paper presents a finite strain constitutive model to predict a complex elastoplastic deformation behaviour involves very high pressures and shockwaves in orthotropic materials of aluminium alloys. The previous published constitutive model is used as a reference to start the development in this work. The proposed formulation that used a new definition Mandel of stress tensor to define Hill’s yield criterion and a new shock equation of state (EOS) of generalised orthotropic pressure is further enhanced with Grady spall failure model to closely predict shockwave propagation and spall failure in chosen commercial materials. This hyperelastic-plastic constitutive model is implemented as 1᨞᨟ᨠᨡ 1 1 1 a new material model in the Lawrence Livermore National Laboratory (LLNL)-DYNA3D code of UTHM’s version, named Material Type 92 (Mat92). The implementation of a new EOS that is modified to match the generalised orthotropic pressure including the spall failure is also discussed in this paper. The capability of the proposed constitutive model to capture the complex behaviour of the selected material is validated against range of Plate Impact Test data at 234, 450 and 895 ms impact velocities.